Technology of Synthesis of Opal Matrix Metamaterials; Advanced Materials Research : Radiation and nuclear techniques in material science; Vol. 1084 : Physical-Technical Problems of Nuclear Science, Energy Generation, and Power Industry (PTPAI -2014) - Bagdasarian A.; Samoylovich M.; Mkrtchan A. R. Alpik Rafaelovich; Rinkevich A.; Belyanin A.; Bagdasarian S.; Mkrtchyan A.; Afanasieva A. (Materials Science and Technologies, 2015)
Title screen